Reduced Atherosclerotic Burden in Subjects With Genetically Determined Low Oxidative Stress - Violi, Francesco; Pignatelli, Pasquale; Pignata, Claudio; Plebani, Alessandro; Rossi, Paolo; Sanguigni, Valerio; Carnevale, Roberto; Soresina, Annarosa; Finocchi, Andrea; Cirillo, Emilia; Catasca, Elisa; Angelico, Francesco; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2013)
OBJECTIVE—NADPH oxidase, one of the most important enzymes producing reactive oxidant species, is suggested to play a role in experimental atherosclerosis, but its role in human atherosclerosis is still unclear. We hypothesized that a reduced activity of NADPH oxidase might be linked to a reduced atherosclerotic burden. METHODS AND RESULTS—Thirty-one women carriers of hereditary deficiency of NOX2, the catalytic subunit of NADPH oxidase, were matched for sex and age with 31 controls and 31 obese women. Flow-mediated dilation and intima-media thickness, 2 surrogate markers of atherosclerosis, serum activity of NOX2, urinary isoprostanes, serum levels of nitrite/nitrate, and platelet production of isoprostanes and nitrite/nitrate were determined. Compared with controls (5.7±3.0% and 0.60±0.11 mm), carriers of NOX2 deficiency had higher flow-mediated dilation (9.2±5.0%; P<0.001) and lower intima-media thickness (0.50±0.11 mm; P=0.002), whereas obese women had lower flow-mediated dilation (3.2±2.1%; P=0.007) and higher intima-media thickness (0.71±0.15 mm; P<0.001). Compared with controls, carriers of NOX2 deficiency had lower urinary isoprostanes (132.6±87.3 versus 82.3±46.0 pg/mg creatinine; P=0.007) and serum NOX2 activity (24.9±19.3 versus 12.8±11.9 pg/mL; P=0.004) and higher serum nitrite/nitrate (23.8±7.6 versus 30.5±6.3 µmol/L; P<0.001), whereas obese women had higher urinary isoprostanes (132.6±87.3 versus 182.2±84.6 pg/mg creatinine; P=0.008) and serum NOX2 activity (24.9±19.3 versus 36.1±18.6 pg/mL; P=0.008) and lower serum nitrite/nitrate (23.8±7.6 versus 12.6±4.2 µmol/L; P<0.001). Flow-mediated dilation correlated with intima-media thickness (r=–0.433; P<0.001), serum NOX2 activity (r=–325; P<0.001), and urinary isoprostanes (r=–0.314; P=0.002). Ex vivo study showed that, compared with controls, platelets from carriers of NOX2 deficiency had lower isoprostanes (P<0.001) and higher nitrite/nitrate (P<0.001), whereas platelets from obese women had higher isoprostanes (P<0.001) and lower nitrite/nitrate (P=0.013). CONCLUSION—The study shows reduced atherosclerotic burden in carriers of NOX2 deficiency, suggesting that oxidative stress generated by this enzymatic pathway is implicated in human atherosclerosis.